Uji Toksisitas dan Aktivitas Antimalaria Melalui Penghambatan Polimerisasi Hem Fraksi Etil Asetat, N-Heksan dan - Lendawati, Lendawati; Yuniza, Filia; Hartanti, Hartanti (Jurnal Analis Kesehatan, 2023)
The population at risk of developing malaria in the Asian region is 1.4 billion people. Nine countries are at high risk of developing malaria in the Asian region where the highest proportion is achieved by India 89%, Myanmar 2% and Indonesia 7%. Inhibition of heme polymerization is an initial screening test for antimalarial activity. Bidara leaves (Ziziphus mauritiana L.) were selected based on the content of secondary metabolites containing alkaloids. Plant compounds that have been shown to have heme polymerization inhibitory activity are phenolic compounds such as flavonoids, anthraquinones, tannins, saponins, terpenoids, alkaloids, and glycosides. This study aims to determine the chemical content and inhibition activity of heme polymerization based on the IC50 value of the N Hexane, Ethyl Acetate and ethanol fractions of bidara leaves (Ziziphus mauritiana L.). The research method was carried out using the modified Basilico method. Heme polymerization inhibition activity is expressed in 50% Inhibition Concentration (IC50), which is the extract level that can inhibit heme polymerization up to 50%. IC50 data showed that the lowest average IC50 value of the ethyl acetate fraction was 1.107 mg/mL, which means that the ethyl acetate fraction of bidara leaves with a concentration of 1.107 mg/mL could provide 50% inhibition. Followed by an average IC50 of the N Hexane fraction of 3.052 mg/mL and an average IC50 value of chloroquine diphosphate of 8.059 mg/mL. Meanwhile, the ethanol fraction of bidara leaves has an IC50 value above the positive control, which is 21.815 mg/ml.